1992
DOI: 10.1203/00006450-199212000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Status of Term Infants Fed Breast Milk or Infant Formula Containing Soy Oil or Corn Oil

Abstract: ABSTRACT. The objective of this study was to compare circulating lipid docosahexaenoic acid [22:6(n-3), DHA] levels in term infants fed a powdered (CORN oil) or liquid (SOY oil) infant formula or human milk (HM). Infants whose mothers chose not to breast feed were randomly assigned to the CORN or SOY formula group. The formula fat differed in linolenic acid [18:3(n-3)] content: it was 0.8% for the CORN and 4.8% for the SOY. Linoleic acid [18:2(n-6)] was 31.5 and 34.2% fatty acids in the CORN and SOY formula, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 20 publications
8
69
0
1
Order By: Relevance
“…Some studies have attempted to optimize LNA to DHA conversion by providing suf®cient LNA (b 0.7% of total energy) and a lower LA to LNA ratio in formula (`10:1). Initial results by Ponder et al (1992) indicated that this alternate strategy could be simpler and less expensive than the addition of n-3 LCPUFA. Studies by Innis et al (1994Innis et al ( , 1996Innis et al ( , 1997 concluded that the need for DHA supplementation should not be based on the alleged improved visual acuity of breast fed infants since despite differences in DHA content in blood no differences in preferential looking acuity between BF and unsupplemented formula fed infants were found.…”
Section: Studies In Term Infants Fed Efa-controlled Dietsmentioning
confidence: 99%
“…Some studies have attempted to optimize LNA to DHA conversion by providing suf®cient LNA (b 0.7% of total energy) and a lower LA to LNA ratio in formula (`10:1). Initial results by Ponder et al (1992) indicated that this alternate strategy could be simpler and less expensive than the addition of n-3 LCPUFA. Studies by Innis et al (1994Innis et al ( , 1996Innis et al ( , 1997 concluded that the need for DHA supplementation should not be based on the alleged improved visual acuity of breast fed infants since despite differences in DHA content in blood no differences in preferential looking acuity between BF and unsupplemented formula fed infants were found.…”
Section: Studies In Term Infants Fed Efa-controlled Dietsmentioning
confidence: 99%
“…Many studies have tested different a-linolenic acid (ALA) supplying formulas in term or preterm infants. They have demonstrated lower plasma and/or RBC DHA levels than with human milk (Innis et al, 1990;Birch et al, 1992;Ponder et al, 1992) and have raised concerns as to the neonate's ability to desaturate and elongate ALA to DHA. For this reason, preformed LCPUFAs have been preferred as supplements to infant formulas (Koletzko et al, 1989;Birch et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57][58] Adding oils containing DHA and ARA to infant formulas in amounts approximating those in human milk results in ''normalization'' of the plasma and RBC DHA and ARA to levels within the range of those in breast-fed infants. [54][55][56] The increase in plasma and RBC DHA and ARA after an increase in dietary DHA and ARA intake is wellknown from studies in adults.…”
Section: Polyunsaturated Fatty Acid Metabolismmentioning
confidence: 99%